Transcription, Processing, and Decay of Mitochondrial RNA in Health and Disease - Barchiesi, Arianna (Int J Mol Sci, 2019)
Although the large majority of mitochondrial proteins are nuclear encoded, for their correct functioning mitochondria require the expression of 13 proteins, two rRNA, and 22 tRNA codified by mitochondrial DNA (mtDNA). Once transcribed, mitochondrial RNA (mtRNA) is processed, mito-ribosomes are assembled, and mtDNA-encoded proteins belonging to the respiratory chain are synthesized. These processes require the coordinated spatio-temporal action of several enzymes, and many different factors are involved in the regulation and control of protein synthesis and in the stability and turnover of mitochondrial RNA. In this review, we describe the essential steps of mitochondrial RNA synthesis, maturation, and degradation, the factors controlling these processes, and how the alteration of these processes is associated with human pathologies.